Digital Echoes: Unraveling the Transnational Spread of Far-Right Ideologies through the Identitarian Movement's Social Media Strategies - Kuncoro, Hestutomo Restu (Jurusan Ilmu Hubungan Internasional, 2024)
The rise of far-right movements globally, exemplified by the Identitarian Movement, underscores the significance of social media in political mobilization and ideological dissemination. This research addresses the question: How does the Identitarian Movement utilize social media affordances to propagate its ideologies transnationally? Through a qualitative case study approach, this study analyzes secondary data from reports, books, and academic databases, focusing on the Identitarian Movement's strategic use of platforms like Twitter, YouTube, Facebook, and Telegram. The findings reveal that the movement exploits social media affordances of visibility, editability, persistence, and association to craft and disseminate high-impact, visually appealing content designed to engage and radicalize audiences. The